2016
DOI: 10.1037/hea0000246
|View full text |Cite
|
Sign up to set email alerts
|

“It’s sort of a lifeline”: Chronic obstructive pulmonary disease patients’ experiences of home telehealth.

Abstract: Users generally describe home telehealth in positive terms; however, patients still value face-to-face contact with health care professionals. The positive aspects of home telehealth, such as better access to health care and providing peace of mind, could be communicated to prospective users to improve uptake. Similarly, sustained use of telehealth is likely to be ensured if occasional visits from health care professionals are maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 27 publications
3
80
0
Order By: Relevance
“…Telehealth can empower patients to self-manage their condition through facilitating increased knowledge of the condition and its symptoms [25], which supports the argument that participants in this study gained knowledge, became better at managing their condition, and triggered fewer alerts. However, it is also argued that telehealth may increase dependence on health care services, with reassurance provided through being “watched over” by health care professionals and the knowledge that they will intervene if something goes wrong [24].…”
Section: Discussionsupporting
confidence: 73%
“…Telehealth can empower patients to self-manage their condition through facilitating increased knowledge of the condition and its symptoms [25], which supports the argument that participants in this study gained knowledge, became better at managing their condition, and triggered fewer alerts. However, it is also argued that telehealth may increase dependence on health care services, with reassurance provided through being “watched over” by health care professionals and the knowledge that they will intervene if something goes wrong [24].…”
Section: Discussionsupporting
confidence: 73%
“…Availability of an HCP mediated by TM technology provided the patients with a more predictable daily life (Barken et al, ). Follow‐up by TM also led to a reduction in health care needs (Gorst et al, ), was more personal (Barken et al, ; Fairbrother et al, ), and was experienced as an improvement over standard care (Fairbrother et al, ; Gorst et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients in nine of the studies (Table ) found that assessing clinical measurements provided them with an insight into their health, which in turn increased their awareness of their individual data. Furthermore, regular measurements increased their clinical understanding of their illness (Gale & Sultan, ; Gorst et al, ) and encouraged them to become more involved and engaged (Barken et al, ), thereby promoting a more structured approach to their health (Huniche et al, ; Williams et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, self‐management is highlighted as an important aspect for individuals living with COPD to become more active and involved in their illness (Simpson & Rocker, ). Further, several studies (Gorst et al., ; Vatnøy et al., ; Williams et al., ) have emphasised that TM can promote self‐management.…”
Section: Discussionmentioning
confidence: 99%